Qualidade do tambaqui (Colossoma macropomum) armazenado em gelo: métodos sensoriais, físico-químicos e microbiológicos - SILVA, Márcio Luís Pontes Bernardo de (2014)
This study aimed to develop a scheme based on the Quality Index Method (QIM) to tambaqui (Colossoma macropomum) raw stored in ice that determines its shelf life. It was studied 96 specimens of tambaqui captured with fishing net and slaughtered (killed) by hypothermia in ice and water , it was packed in ice boxes and kept on ice in a 1:1 (Kg fish/ice) ratio at a controlled temperature of 0 ± 1 ° C for 24 days. Fishes were evaluated at time 01 , 03 , 05 , 08 , 10 , 12 , 15 , 17 , 19 , 22 , 24 day of ice storage. After sensory, physical-chemistry and microbiological analyses the developed scheme presented 04 quality attributes with a total of 30 points. The pH showed little variation from 6.52 to 6.71, from the beginning to end of the experiment. The average content of BVT changed from 15.23 mg N.100g- 1 to 23.17 mg N.100g- 1 and it did not reach the amount considered unsafe for consumption. Mesophilic, and Psicotrophic bacteria remained with their values below log 106. The experiments with Pseudomonas and Enterobacterias showed their values below the limit recommended by the World Health Organization (WHO) that is log 107, and it was demonstrated by producer bacteria H2S a growth of values reduced throughout the experiment. Then the method proved to be efficient to assess the loss of sensory quality related to the length of time in storage and it indicated an expiration date of 22 days which determine the shelf life of tambaqui. Microbiological analyzes with specific bacterial counts of deteriorating organisms strengthen the sensory results and it suggests the tambaqui (Colossoma macropomum) raw stored in ice is fit for consumption until the 22nd day.